Trade and the environment in the context of the World Trade Organization (UN ECLAC Port of SpainTT, 1998)
Examines the issues involved in the current debate on trade and the environment. Gives a summary of the conclusions and recommendations contained in the report of the WTO Committee of Trade and the Environment and examines some of the issues in the context of recent Caribbean trade policies.
Bibliography: p. 17-18